ENERGY COOPERATION OF THE POST-SOVIET STATES - Valeria A. Romashkina (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article defines the opportunities and directions for the development of regional energy integration of the Post-Soviet countries. It highlights the features and prospects for the oil and gas industry development both of net exporters and net importers of energy resources. Considers joint investment projects in the energy sector within the CIS, as well as with China, Iran and other states. Notes the main risks for Russia's positions in connection with the development of oil and gas fields of the Caspian Sea. The author defines ways of increasing the level of cooperation and integration of the countries of the Post-Soviet space in the oil and gas sectors, electric power industry and renewable energy.